Effects of Nurse Case Manager and Multidisciplinary Clinical Pathway for Type 2 Diabetic Patients, Lop Buri Hospital - Boonploy, Valai; Manit, Ananya (Journal of Health Science of Thailand, 2018)
This quasi-experimental research was aimed at testing effects of nursing service system coordinated by nurse case manager and multidisciplinary care followed the clinical pathway for type 2 diabetic patients with hypoglycemia on quality of diabetes care including blood sugar, length of hospital stay, cost of diabetes care and readmission. The samples included sixty type 2 diabetes patients with hypoglycemia admitted in Lop Buri Hospital. Thirty subjects were randomly assigned to each an experimental group and a comparative one. The experimental group received the multidisciplinary care that followed the clinical pathway for diabetic patients with hypoglycemia and coordinated by a nurse case manager. The control group received only routine care. The patients profile and diabetes care quality data were recorded on diabetes care quality form by nurse case managers. Data was analyzed using descriptive statistic, independent t-test and Mann Whitney U test The finding revealed that the experimental group had significantly lower mean blood sugar level than that of the control group (96.67 mg% vs 102.68 mg%, p<0.05). The mean rank of length of hospital stay of the experimental group was significantly lower than that of the control group (24.10 days vs 36.90 days, p<0.05). Diabetic care cost of the experimental group was significantly lower than that of the control group (4,195.40 baht vs 6,375.53 baht, p<0.05). In addition, mean rank of patients who were readmitted within 28 days of the experimental group was significantly lower than that of the comparison group (27.50 vs 33.50, p<0.05) This study suggests that the nursing service system coordinated by nurse case manager and the multidisciplinary care followed the clinical pathway for type 2 diabetic patients with hypoglycemia can improve quality of diabetic care.